2017
DOI: 10.3389/fmicb.2017.01468
|View full text |Cite
|
Sign up to set email alerts
|

Rab5 Enhances Classical Swine Fever Virus Proliferation and Interacts with Viral NS4B Protein to Facilitate Formation of NS4B Related Complex

Abstract: Classical swine fever virus (CSFV) is a fatal pig pestivirus and causes serious financial losses to the pig industry. CSFV NS4B protein is one of the most important viral replicase proteins. Rab5, a member of the small Rab GTPase family, is involved in infection and replication of numerous viruses including hepatitis C virus and dengue virus. Until now, the effects of Rab5 on the proliferation of CSFV are poorly defined. In the present study, we showed that Rab5 could enhance CSFV proliferation by utilizing le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Accumulating evidence indicates that CSFV is transmitted from early endosomes (Rab5-dependent) to late endosomes (Rab7-dependent) and then into lysosomes [31,32]. Rab5 has been shown interact with CSFV NS4B to enhance CSFV replication by facilitating formation of NS4B complexes [43]. In this study, we found that IFITMs partly colocalized with Rab5, Rab7, and Lamp1.…”
Section: Discussionsupporting
confidence: 52%
“…Accumulating evidence indicates that CSFV is transmitted from early endosomes (Rab5-dependent) to late endosomes (Rab7-dependent) and then into lysosomes [31,32]. Rab5 has been shown interact with CSFV NS4B to enhance CSFV replication by facilitating formation of NS4B complexes [43]. In this study, we found that IFITMs partly colocalized with Rab5, Rab7, and Lamp1.…”
Section: Discussionsupporting
confidence: 52%
“…Mitogen-activated protein kinase 2 interacts with the main CSFV antigen E2 to promote CSFV growth through attenuation of the Janus kinase/signal transducers and activators of transcription (JAK-STAT) pathway 30 . The Rab5 protein interacts with CSFV NS4B to facilitate the formation of NS4B-related complex 10 , and in Huh7 hepatoma cells, hepatitis C virus (HCV) NS5A interacts with an immunosuppressant FK506-binging protein (FKBP38) to inhibit apoptosis 30 , 31 . We herein report interaction between CSFV NS4B and FHC.…”
Section: Discussionmentioning
confidence: 99%
“…However, a chimeric low-virulence GPE-derived virus carrying the complete Eystrup NS4B sequence showed enhanced pathogenicity and high replication efficiency 9 . In addition, the findings of our previous study indicated that an NS4B-related complex, the formation of which is facilitated by Rab5, is thought to be the CSFV replication complex 10 . Although many studies have focused on the roles of CSFV NS4B in viral virulence and genomic replication, few studies have investigated cellular NS4B-interacting proteins and their roles in CSFV replication.…”
Section: Introductionmentioning
confidence: 88%
“…Rab1A takes part in particle assembly of CSFV [38] and Rab2 can promote CSFV replication [39]. In addition, Rab5 promotes NS4B induced complex formation and thereby increases CSFV replication [40]. However, the effects of Rab25 on CSFV replication have received little attention.…”
Section: Discussionmentioning
confidence: 99%